Peningkatan Prestasi Belajar IPA melalui Model Pembelajaran Group Investigation (GI) Masa Covid-19 pada Siswa Kelas VII-A SMPN 3 Masbagik - Karyawati, Bq (MASALIQ, 2021)
This research is a classroom action research (CAR) aimed at improving science learning achievement which is carried out in class VII-A students of SMPN 3 Masbagik by using the Model Group Investigation (GI). The researcher conducted an action research with the aim of knowing the increase in science achievement in class VII-A SMPN 3 Masbagik through the application of the Group Investigation (GI) learning model. Based on the results of research and discussion of the GI learning model, it can increase the activities and science achievements of class VII-A students of SMPN 3 Masbagik in the odd semester of the 2020/2021 school year. This increase can be seen from the acquisition of student activity scores, teacher activity and class average scores as well as classical completeness levels in each cycle which have increased both in cycle I and cycle II. Based on the results of data analysis in each cycle, it appears that the results from cycle I to cycle II have increased. In the implementation of learning and the results of the first cycle of data analysis, for student activities an average value of 2.84 was obtained and student activities in the second cycle obtained an average class value of 3.85 while classical completeness was obtained in cycle 1 of 66% and increased in cycle 2 by 94%